Isolation, Purification and Evaluation of Antibacterial Agents from Aloe vera - Rubina Lawrence (Brazilian Journal of Microbiology, 2009)
The ethanol, methanol and acetone extracts of Aloe vera gel were studied for their antimicrobial activity against four Gram-positive and Gram-negative bacteria using agar well diffusion method. The extracts showed varied levels of antimicrobial activity against the tested pathogens. The ethanol and methanol extracts showed higher activity while acetone extract, showed least or no activity against most of the tested pathogens. Fractions obtained from the extracts by Thin Layer and Column Chromatography were studied for their antagonistic properties using Spot Assay Technique. Compounds with maximum antibacterial activity isolated from the ethanol and methanol extracts were identified as p - coumaric acid (Mol. wt.165), ascorbic acid (Mol. wt.177 ), pyrocatechol (Mol. wt.110 ) and cinnamic acid (Mol. wt.148), on the basis of Gas Chromatography Mass Spectrometry. The study suggests the antimicrobial activity of the A. vera gel extract to be dependant on the synergistic effect of different compounds. With the broad spectral antimicrobial effect of A. vera gel, it could be further recommended in the treatment of various bacterial diseases.